Potencial de produção de cana-energia em áreas agrícolas marginais no Brasil - Violante, Mauro Henrique Salgueiro Rodrigues (2012)
The discovery and use of oil caused significant changes in society over time, being one of the most important factors and environmental and cultural transformation in the world over the last century. Its wide range of possibilities for use ended up creating a production system based on a single energy agent, especially in countries which do not have water resources or other renewable sources. However, in the last decades of the last century, countless discussions about the need to change the composition of the global energy matrix have arisen. As a result of concerns about the shortage of natural resource, several researchers directed their studies for the search for alternatives that could sustainably provide a substitute to oil. One would be the use of biomass in order to take advantage of the ability of plants to transform solar energy into carbohydrates. Brazil, in addition to owning one of the most diversified clean energy matrices in the world, has large expanse of arable land which puts it in a prominent position on the production potential of agroenergetic cultures. Considering the characteristics of sugar cane and its adaptation to growing areas of Brazil and driven by the demands of modern biomass production, to be applied in more complex transformation processes and allow obtaining other products besides sugar, alcohol and energy, this paper studied plants of improved sugar cane with the sole purpose of producing modern biomass, the so-called 'energy cane' (sugar cane energy). This is a plant that, contrary to traditional sugarcane, improved to produce sucrose, is directed to produce fiber, and that, in addition, by having greater participation of the ancestral species of greatest rusticity, are able to withstand stressful environmental conditions. The results obtained have shown that the hybrids have large cane energy potential of biomass production and dry mass per area, at highly competitive costs considering the comparative analysis of cost of production of dry mass per area. As for production, it was possible to observe that in addition to being more productive in first cut, on the results of ratoon crop (second cut), the better sugarcane hybrid came to produce energy, one and a half times more drought mass than the traditional sugar cane, and presented the biggest productivity that other energy crops such as the eucalyptus and the elephant grass, being that, considering the average yields observed from the third cut with these productivity levels, energy cane becomes the raw material with lower production cost of dry mass per area, showing its high potential as raw material for the production of bioenergy. In the agroecological zoning for energy cane, it has been possible to identify 32.3 million hectares of marginal agricultural production areas suitable for the cultivation of this material, which according to the results of the agricultural zoning and the characteristics of the regions in studies, shows that from this total, we can consider that the material under study in this paper, could be grown at least 2.0 to 8.0 million hectares with sugar cane energy of this first generation of hybrids.